Calidad microbiológica de pescado en venta en la Ciudad de Guatemala - de León, Roberto (1978)
Esta investigación fue financiada por el Centro lnternacional para el Desarrollo de Recursos Marinos de la Universidad de Rhode Island, Kingston, R.l., EE.UU.   Abstract A sanitary microbiological survey of fresh and processed fish on sale in Guatemalan markets and supermarkets was carried out. Samples of tables, floor and freezer surfaces, and of the water, ice and liquid drippings of the different stands were also taken and analyzed. Aerobic counts exceeded 106/g in 72% of the samples, and 16% had more than 40 fecal coliforms/g. Coagulase-positive Staphylococcus aureus were never higher than 100/g in fish. The bacterial counts were higher in the ice and liquid drippings.